Adenosine A2A Receptors Shut Down Adenosine A1 Receptor-Mediated Presynaptic Inhibition to Promote Implementation of Hippocampal Long-Term Potentiation - Lopes, Cátia R. (2023)
Adenosine operates a modulation system fine-tuning the efficiency of synaptic transmission and plasticity through A1 and A2A receptors (A1R, A2AR), respectively. Supramaximal activation of A1R can block hippocampal synaptic transmission, and the tonic engagement of A1R-mediated inhibition is increased with increased frequency of nerve stimulation. This is compatible with an activity-dependent increase in extracellular adenosine in hippocampal excitatory synapses, which can reach levels sufficient to block synaptic transmission. We now report that A2AR activation decreases A1R-medated inhibition of synaptic transmission, with particular relevance during high-frequency-induced long-term potentiation (LTP). Thus, whereas the A1R antagonist DPCPX (50 nM) was devoid of effects on LTP magnitude, the addition of an A2AR antagonist SCH58261 (50 nM) allowed a facilitatory effect of DPCPX on LTP to be revealed. Additionally, the activation of A2AR with CGS21680 (30 nM) decreased the potency of the A1R agonist CPA (6-60 nM) to inhibit hippocampal synaptic transmission in a manner prevented by SCH58261. These observations show that A2AR play a key role in dampening A1R during high-frequency induction of hippocampal LTP. This provides a new framework for understanding how the powerful adenosine A1R-mediated inhibition of excitatory transmission can be controlled to allow the implementation of hippocampal LTP.